Dimensional Structure of and Variation in Anthropomorphic Concepts of God - Shaman, Nicholas J.; Saide, Anondah R.; Richert, Rebekah A. (Frontiers in Psychology, 2018)
When considering other persons, the human mind draws from folk theories of biology, physics, and psychology. Studies have examined the extent to which people utilize these folk theories in inferring whether or not God has human-like biological, physical, and psychological constraints. However, few studies have examined the way in which these folk attributions relate to each other, the extent to which attributions within a domain are consistent, or whether cultural factors influence human-like attributions within and across domains. The present study assessed 341 individuals’ attributions of anthropomorphic properties to God in three domains (psychological, biological, and physical), their religious beliefs, and their engagement in religious practices. Three Confirmatory Factor Analyses tested hypothetical models of the underlying structure of an anthropomorphic concept of God. The best fitting model was the “Hierarchical Dimensions Concept,” the analyses indicated one overall dimension of anthropomorphism with three sub-domains. Additionally, participants’ religiosity was negatively related to attributing human-like psychological properties to God, suggesting that the more people engage with their religion, the less they think about God as having a ‘human-like’ mind. Religiosity was positively related to individual consistency scores in the biological domain. In other words, greater religiosity was related to less consistent answers about God’s biological properties. As a result, the findings of the current study also suggest that individuals do not just vary between each other in how much they anthropomorphize God, but additionally, variation exists in the type of anthropomorphic reasoning used within an individual person’s concept of God.